Minimum Wage Competition between Local Governments in China - Yanan Li; Ravi Kanbur; Carl Lin (Institute of Labor Economics (IZA), 2018)
The theory of fiscal and regulatory competition between jurisdictions is more advanced than its empirical testing. This is particularly true of labor regulation in general, and minimum wage regulation in particular, and especially so for developing countries. This paper utilizes the spatial lag methodology to study city-level strategic interactions in setting and enforcing minimum wage standards during 2004-2012 in China. We manually collect a panel data set of city-level minimum wage standards from China's government websites. This analysis finds strong evidence of spatial interdependence in minimum wage standards and enforcement among main cities in China. If other cities decrease minimum wage standards by 1 RMB, the host city will decrease its standard by about 0.7-3.2 RMB. If the violation rate in other cities increases by 1 percent, the host city will respond by an increase of roughly 0.4-1.0 percentage points. The results are robust to using three estimation methods, Maximum Likelihood, IV/GMM and a dynamic panel data model. Our findings of strategic interactions suggest the need for policy coordination in labor regulation in China.
Keywords: J38; 330; minimum wage; enforcement; race to the bottom; strategic interactions; China